Dampak Perceraian Pada Anak Di Gereja Bethel Indonesia Wilayah Jakarta Barat - Djamino Widi Sulistija; Stephanus Karnadhi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Divorce is a reality that occurs in the church with various complex causal factors ranging from economic problems, domestic violence, infidelity, quarrels and several other causes. Divorce causes deep emotional wounds and various deviant behaviors in both children and their parents. Children become sensitive individuals, easily angered, depressed and even have suicidal tendencies. This research was conducted at five GBIs located in West Jakarta. The research sources were five people from teenagers to adults whose parents were divorced. This type of research is field research and the author uses qualitative methods. The research results show that divorce is indiscriminate, it can happen to congregations and servants of God. The divorce that occurred in five GBIs gave rise to complex deviant behavior such as LGBT and suicidal thoughts. The author's findings show that the problem of parental divorce does not cause children to abandon their worship as much as 80% of respondents and only 20% have a major impact. Meanwhile, at school, there was no visible decline in children's grades. As many as 80% of respondents showed good enthusiasm for learning and achieving achievements at school. The remaining 20% ​​of their learning achievement decreased. From this analysis it can be concluded that the impact of divorce on children's worship and school grades is very small.